PELAKSANAAN PROGRAM PENDIDIKAN PELATIHAN DI DINAS TENAGA KERJA TRANSMIGRASI DAN KEPENDUDUKAN PEMERINTAH PROPINSI JAWA TIMUR - Yuli Kartika Efendi (Khazanah Pendidikan, 2017)
National education consists of three subsystems are subsystems of formal education, informal and non-formal. In order to provide supplies to the community to compete in the field of labor and to increase revenue, One of the earliest of this type of non-formal education is training, training activities provide considerable benefits for trainees, and if managed properly. Government UPTPK Pasuruan Pasuruan through implementing various vocational skills training / skills. UPTPK Pasuruan as one yag Technical Implementation Unit under and is responsible to the Department of Labor East Java province. The tasks of UPTPK Pasuruan is implementing occupational skills training in order to provide a skilled workforce, productive and independent. Implementation of the training program is divided into three, namely: (1) Training held institutionally namely in UPTPK Pasuruan themselves every day to work, (2) Exercise Non Institutional (MTU) executed in mobile / roving by request Local Government / Agency / Society, (3) the training program third parties or self-financing, with longer workouts tailored to its agreements da fees charged to students in accordance with the agreement. Keywords: Program, Education, Training